Crop diversity measurement at Dufuya gardens and Insukamini irrigation scheme in Lower Gweru communal lands - Matsa, Mark (David Publishing, 2014)
Dufuya wetland and Insukamini irrigation in Lower Gweru communal land of Gweru district are two examples on how rural communities can be self reliant when they are capacitated. This study sought to compare crop diversity between these two vegetable producing schemes. The location of the two areas and the selected plots were determined using the GPS (global positioning system) hand receiver. Maps of the quadrants were produced in a GIS (geographic information system) on a computer. Simpson’s index D = sum (Pi2) was used to measure crop diversity while the Shannon-Weiner index (H) was used to measure crop evenness. Results show that although both schemes are viable, Dufuya Gardens have higher crop diversity than Insukamini irrigation scheme. The study recommends that AGRITEX officers at Insukamini must advise farmers to diversify their crops in order for their produce to be more competitive on the market and also to cushion farmers against the effects of natural hazards. Given the success of the two schemes, the government must seriously consider sustainable utilization of the many small-scale dams and wetlands lying idle across the country for crop production in order to empower poor rural communities as well as alleviate poverty